Unusual manifestation of vitamin A deficiency presenting with generalized xerosis without night blindness - Pariya Phanachet (2019)
© 2018 The Authors. Clinical Case Reports published by John Wiley & Sons Ltd. Vitamin A deficiency from malabsorption syndromes, including bariatric surgery, has become an emerging problem in developed countries. Early detection and prompt treatment lead to rapid and complete recovery. Nevertheless, it may result in irreversible blindness or death if left untreated. Health care personnel should be aware of this condition.